ENT 530 Social Media Portfolio / Nurul Fatin Farhanis Muhamad Zakir - Muhamad Zakir, Nurul Fatin Farhanis (2019)
Sky S.oul is a new company that offered a very special, unique, affordable and healthy foods for all range of ages and for all kind of people. We make someone who loves seafood enjoy the taste of it in a simple way without stressed about how to find it and how much time they need to sacrifice to prepare for it. This company sells Yong Tau Foo with a various choices of items and they will be served with 3 choices of base. Emphasis is placed on high - favourable products driven by preference of individuals.